Plan de gestión de manejo de visitantes dentro del bosque protector “Cascada de Peguche” - Males Jara, Zuni Andrea (2023)
The Peguche waterfall protective forest in the city of Otavalo, is a natural space that is located in the rural area of the canton, and that has been considered a tourist and cultural destination, due to the spiritual implication it has with the indigenous ethnic group, This has allowed it to be very attractive to a large number of tourists who, over time, have generated a negative impact on the surroundings and environment of the sector, additionally the absence of administrative and tourist management has allowed the problem to be more serious. Therefore, in the present investigation, the purpose was to develop a proposal for the management and management of visitors that allow the sustainability of the sector. The methodology used was descriptive with a qualitative and quantitative approach, the necessary information was obtained from an interview with the President of the community responsible for the care of the sector and surveys of visitors, finding as results that the majority of visitors are families, with high frequency. of concurrence, the existing signage is deteriorated and is insufficient to guide towards a good behavior and use of the infrastructure. It is necessary to manage financial resources to make improvements and issue behavioral regulations for visitors. It concludes in the realization of a Tourism Management Manual which must be approved by the community and executed by it.